2015
DOI: 10.1002/jso.24004
|View full text |Cite
|
Sign up to set email alerts
|

Surgery of gastric cancer and esophageal cancer: Does age matter?

Abstract: An exclusion from surgical therapy due to advanced age in general seems not to be justified. However, the decision for a surgical resection in patients over 80 years should be made with caution. pNM-categories and R0-resection remain the most important predictive factors for overall survival in all subgroups. No survival benefit for neoadjuvant treatment in patients over 70 years was found, while women survived longer than men. However, the decision concerning a (radio) chemotherapy should be made individually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…However, we cannot rule out a selection bias as fewer patients older than 70 years underwent a thoracoabdominal approach. Previously we have shown that age does not influence survival in our patient cohort [41], yet in this cohort patients who were older than 70 years at the time of diagnosis had shorter survival times. As only a few patients older than 70 years were resected by TAE, we performed a subgroup analysis including only patients younger than 70 years for better comparability, confirming the prognostic influence of the type of surgery for this subgroup, and we identified the type of surgery as an independent prognostic factor in multivariate analysis in the cohort of patients younger than 70 years.…”
Section: Discussionmentioning
confidence: 46%
“…However, we cannot rule out a selection bias as fewer patients older than 70 years underwent a thoracoabdominal approach. Previously we have shown that age does not influence survival in our patient cohort [41], yet in this cohort patients who were older than 70 years at the time of diagnosis had shorter survival times. As only a few patients older than 70 years were resected by TAE, we performed a subgroup analysis including only patients younger than 70 years for better comparability, confirming the prognostic influence of the type of surgery for this subgroup, and we identified the type of surgery as an independent prognostic factor in multivariate analysis in the cohort of patients younger than 70 years.…”
Section: Discussionmentioning
confidence: 46%
“…Nienhueser and colleagues instead found that, although postoperative medical complications were more frequent in patients aged more than 70 years, multivariate analysis did not select age as a prognostic factor for surgical complications, which were instead related to ASA III-IV, abdomino-thoracic resection and pre-existing comorbidities, indicating that age alone is no contraindication for resection of gastric cancer if the patient fits for extended surgery (38).…”
Section: Extent Of Lymphadenectomy In Elderly Gastric Cancer Patientsmentioning
confidence: 96%
“…If Degiuli found no significant difference in OS after D1 versus D2 lymph node resection in elderly patients (42), Nienhueser, observed a worsening in OS only for patients aged more than 80 years, with no statistically significant differences in surgical complications between patients aged more or less than 80 years (38).…”
Section: Extent Of Lymphadenectomy In Elderly Gastric Cancer Patientsmentioning
confidence: 99%
“…The higher age of our cohort might have contributed to the shorter survival times, with a median age of 73 years in our patients and 43% of the patients being ≥75 years old, whereas Lorenzen et al [17] included patients from the age of 65 years with a median age of 70 years (no data of the number of patients >75 years old available). Regarding the palliative situation, where comparable survival times with systemic chemotherapy have been found for patients younger and older than 75 years [28], and considering the recent results of Nienhueser et al [23] who found an inferior survival and a significantly increased in-hospital mortality rate for very old patients undergoing surgery for esophagogastric cancer, we believe that the surgical procedure contributed to the decreased survival of our older age group rather than the chemotherapy itself.…”
Section: Discussionmentioning
confidence: 99%
“…However, oncologists are often reluctant to offer neoadjuvant systemic treatment to elderly patients, fearing increased toxicity rates and clinical deterioration, which precludes a potentially curative surgical procedure as a worst-case scenario. At our institution, only approximately 25% of all patients aged ≥70 years with esophagogastric cancer who undergo resection at the surgical department of the University Hospital Heidelberg are treated with neoadjuvant intention, which is a significantly lower number than for the younger patients (41%) [23]. …”
Section: Discussionmentioning
confidence: 99%